1970
DOI: 10.1139/v70-088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the rate of solvolysis of t-butyl chloride in ethanol-water mixtures

Abstract: The effect of pressure on the rate of spontaneous solvolysis of t-butyl chloride in ethanol-water mixtures in the range 0 to 40% v/v ethanol at 0 -C has been measured up to a maximum pressure of 3 kbar. The results have been examined from several points of view and the conclusions are briefly described in the summary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…A possibility which deserves consideration is whether or not the data could be better represented by a polynomial of higher than second order (see ref. 20). In view of the fact that most of the deviations shown in Fig.…”
Section: The Volume Of Activationmentioning
confidence: 95%
“…A possibility which deserves consideration is whether or not the data could be better represented by a polynomial of higher than second order (see ref. 20). In view of the fact that most of the deviations shown in Fig.…”
Section: The Volume Of Activationmentioning
confidence: 95%
“…Without further justification at this point we assume that a quadratic relationship between 111 k and p is sufficient for the purpose of evaluating the error in k due to uncertainty in pressure. Accordingly, differentiation of [7],…”
Section: Determination Ofthe Error Itz Kmentioning
confidence: 99%
“…Various methods have been suggested, including the use of polynomial In k vs. p functions (6), incremental extrapolation (7), and by assuming that the volume of activation has a functional dependence upon pressure approximated by the empirical Tait equation (8,9), which has been found to represent satisfactorily the PVT properties of many real substances.…”
Section: Introductionmentioning
confidence: 99%
“…The plot is clearly non-linear demanding at least a second-order function to describe the dependence of In k uponp. The problem of deriving an analytical expression for this dependence has been discussed at length by various workers (7,8). Golinkin, Laidlaw, and Hyne (7) concluded that the quadratic function provided the best representation of the dependence of In k uponp for benzyl chloride solvolysis in aqueous alcohols.…”
Section: P ( a T M )mentioning
confidence: 99%
“…It should be stressed at this point that the uncertainties listed in Table 2 are those obtained on the basis that eq. [2] represents the correct functional dependence of In k upon p. Since this question is subject to considerable controversy (7,8), the actiial uncertainty in A Vo* is probably greater than that calculated from the least-mean square fit of the ratelpressure data to eq. [2].…”
mentioning
confidence: 99%